Interrogation in Ukrainian Criminal Procedure - Hloviuk, Iryna (Teisė, 2022)
The aim of the paper is to research the interrogation in Ukrainian criminal procedure with a particular focus on the use of pretrial testimonies in trial. The author seeks to identify the main problems of procedure of interrogation and grounds of use testimonies in trial. The draft amendments of interrogation and doctrine views are discussed. The conclusions of article are the propositions for review of the use of pretrial testimonies in trial for testimonies of children and testimonies in wartime.